Pembentukan Model Pengakuan Sewa Yang Ideal Berdasarkan PSAK 73 Untuk Meningkatkan Kinerja Keuangan Perusahaan Jasa Transportasi di Indonesia - Duwi Rahayu; Imelda Dian Rahmawati; Aisha Hanif (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this study is to obtain information related to the formation of an ideal rental recognition model based on PSAK 73 to improve the financial performance of transportation service companies in Indonesia. This research is a qualitative research using a content analysis approach. The content analysis approach in this study uses secondary data and information from the financial statements of transportation service companies in Indonesia that present periodic financial reports on the Indonesia Stock Exchange in 2018, 2019, 2020 and the third quarter of 2021. Based on the availability of data, the sample of this research is 3 The transportation company with the largest number of shares outstanding on the Indonesian stock exchange is sourced from www.idx.co.id and has implemented PSAK 73 before and after January 1, 2020. The results of this study indicate the establishment of a rental recognition model for transportation companies in Indonesia based on PSAK 73 has been applied ideally implied in the company's statement of financial position. However, the implementation of PSAK 73 is not overall able to improve the financial performance of transportation service companies in Indonesia due to the reclassification of accounts into Right to Use Assets and Lease Liability which could potentially increase the company's total liabilities. This study shows that companies need to make policies to reduce risks related to the application of PSAK 73, especially for transportation service companies in Indonesia.